The Cross-Border Insolvency in the Execution of Bankrupt Assets Outside Indonesian Jurisdiction: A Comparative Study with Malaysia, Singapore, and the Philippines - Putu Eka Trisna Dewi (IKAT: The Indonesian Journal of Southeast Asian Studies, 2021)
Insolvency institutions have an important role in realizing legal certainty in the settlement of debt and credit disputes, which is one of the risks that arise from the rapid development of international business transactions. Bankruptcy cases containing foreign elements are called cross-border insolvency. The problems that arise in cross-border insolvency are more complex, especially regarding the execution of assets of bankrupt debtors situated outside Indonesia's jurisdiction. This study uses a doctrinal legal research method with a statutory approach. Bankruptcy in Indonesia is regulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. In this law, the execution of assets of bankrupt debtors outside the jurisdiction of Indonesia has not been regulated so that the curator as the body appointed to carry out the execution cannot carry out the task as mandated by the law. The non-executable assets of the bankrupt debtor outside the jurisdiction of Indonesia have caused the bankruptcy estate (de boedel) ineffective; therefore, creditors do not receive a maximum payment related to debtor's debt. For this reason, Indonesia needs to adopt the UNCITRAL model of law on cross-border insolvency or to make bilateral and/or multilateral agreements that are reciprocal in nature related to the execution of bankrupt debtors' assets located outside Indonesia's jurisdiction.